Relationship between Diet, Cosmetics and Degree of Acne Vulgaris in Dermatovenereology Outpatients at Dr. Soetomo General Hospital, Surabaya - Mah Zhook Yueng; Diah Mira Indramaya; Arifa Mustika (Faculty of Medicine Universitas Padjadjaran, 2018)
Background: Acne vulgaris (AV) is a chronic inflammatory multifactorial disease that involves the pilosebaceous unit. The lesions of acne may be either non-inflammatory (comedones, which are blackheads or whiteheads) or inflammatory lesions (papules, nodules or pustules). The effects of diet and cosmetics on acne are still inconclusive. The objective of this study was to analyse the relationship between diet, cosmetics and the degree of AV.Methods: This was a hospital-based, analytic observational study with cross-sectional design. The subjects were patients from the Outpatient Clinic of Dermatovenereology Department of Dr. Soetomo General Hospital. The questionnaire was filled by the respondents and the degree of AV was graded by the specialist. Results: Among the types of diet, white bread (p=0.039), chocolate (p=0.044) and oily food (p=0.013) are significantly associated with the degree of AV. However, white rice, potatoes and milk were insignificantly related to degree of AV (p>0.05). No significant association was found in cosmetics (cleanser, moisturizer, facial protection, exfoliators and decorative cosmetics) with the degree of AV (p>0.05).Conclusions: The factors that have an influence on the degree of AV are white bread, chocolate and oily food intake.